Experimental and theoretical investigation of transient nitric oxide emission in a turbocharged diesel engine - Chen, Xiansong. (2009)
The problems encountered with turbocharged diesel engines especially for their transient response and exhaust emission characteristics have been examined. To obtain a better understanding of the transient behaviour of turbocharged diesel engines, a dynamic engine test bed complete with instrumentation have been set up in this project. The engine under investigation was a vehicular type with electronically programmable fuel injection control. Extensive base-line tests have been conducted which provide references to those tests under fuel injection controls.